COMMUTER BRIDGE: A Braess Paradox Simulation to Teach Social Dilemmas. (February 2017) - Merlone, Ugo; Romano, Angelo
Background. COMMUTER BRIDGE is a n-person social dilemma game that allows participants to experience situations in which individual rationality leads to collective disaster. Aim. Participants are asked to imagine they are commuters who must every day reach a place in the shortest possible time. Method. The game is divided in two phases: in the first phase, participants can choose between two routes whereas in the second phase they are given a third possibility by the construction of a bridge that, paradoxically, increases traffic. Results and conclusion. Participating in this activity will enhance understanding of social dilemmas, help discover the limitations of communications, and develop insights about personal fallacies in strategic reasoning.